High EIF4E2 expression is an independent prognostic risk factor for poor overall survival and recurrence-free survival in uveal melanoma. (May 2021) - Yang, Binghua; Gu, Aiping; Wu, Yi
Abstract: Uveal melanoma (UM), as the most common primary intraocular carcinoma, is a relatively rare but lethal tumor. Upregulated eukaryotic translation initiation factor 4E family member 2 (EIF4E2) promotes the progression of multiple human carcinomas. However, its role remains unclear in UM. To identify the prognostic value of EIF4E2 in UM, we downloaded RNA-sequencing data along with clinical information from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) datasets. EIF4E2 mRNA was significantly increased in three different subgroups in the TCGA-UM dataset. High mRNA expression was correlated with shorter overall survival (OS) and shorter recurrence-free survival (RFS). Moreover, we constructed a prognostic signature using Cox regression analyses in our training cohort TCGA-UM dataset as follows: risk score = 0.04335 × Age +0.49639 × expression of EIF4E2. Based on the risk score, each patient was classified as high-risk or low-risk. Additional survival analyses suggested that patients in the high-risk score group had an unfavorable OS compared with patients in the low-risk score group, which was validated in two external GEO datasets, including GSE84976 and GSE22138. Functional enrichment analysis demonstrated that UM was correlated with hypoxia-related functions. Gene set enrichment analysis (GSEA) indicated significant enrichments of the p53 and Notch pathways. In addition, EIF4E2 was genetically altered in 12.5% (10/80) of UM patients. Epigenetically, higher expression of cg03852847 was correlated with longer OS and longer RFS. In conclusion, our findings demonstrated that high EIF4E2 expression is an independent prognostic risk factor for UM patients. EIF4E2 might play an important role in hypoxia-related signaling pathways during UM progression. Both genetic and epigenetic alterations may contribute to UM pathogenesis. These findings could offer individualized clinical prognostication and potential novel treatment targets for UM patients. Highlights: The first study of EIF4E2 role in UM prognosis using integrative bioinformatics tools, including TCGA and GEO datasets. High mRNA expression of EIF4E2 suggested an unfavorable overall survival and a short recurrence-free survival. EIF4E2 might function via hypoxia-related signaling pathways to regulate UM progression, offering a novel drug target. Both genetic and epigenetic alterations might contribute to UM pathogenesis.